Cross-level dynamics of collaboration and conflict in multi-party systems: An empirical investigation using a behavioural simulation - Petru Lucian Curseu; Sandra Schruijer (Administrative Sciences, 2018)
Multiparty systems bring together various stakeholder parties and their representatives and offer a platform for sharing their diverse interests, knowledge and expertise in order to develop and realize joint goals. They display complex relational dynamics in which within-party interactions (interpersonal interactions within each stakeholder party) as well as between-party interactions (interactions between the stakeholder parties) intertwine to generate bottom-up and top-down influences. We investigate these influences in a behavioural simulation. Our results show that changes in task conflict at the stakeholder party level positively predict changes in perceived collaborativeness in the overall system, while changes in relationship conflict at the stakeholder party level positively predict changes in perceived conflictuality in the system. Moreover, we show that changes in perceived overall conflictuality leads to a proportional change in relationship conflict experienced within the stakeholder parties.
Keywords: 350; collaboration; conflict; participation; multiparty systems; group dynamics; multilevel analysis